Pengaruh Kunjungan Wisatawan dan Tingkat Hunian Hotel Terhadap Pendapatan Asli Daerah Kota Banda Aceh - Ghufran; Khairul Amri; Hafidhah (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
Tourism has become one of the most significant export sectors in many developing countries. The development of tourism not only increases foreign exchange income but also creates job opportunities, stimulates the growth of the tourism industry, and triggers overall economic growth. Therefore, tourism development has become an important target for most governments, especially in developing countries. Indonesia, as the largest archipelago in the world, has high tourism potential, making it an attractive destination for both domestic and international tourists. Banda Aceh, the capital city of Aceh Province located at the northern tip of Sumatra Island, boasts many impressive tourist destinations. This study aims to analyze the impact of tourist visits, hotel occupancy rates, and guest stay duration on the local revenue of Banda Aceh. The analytical method used in this study is the Autoregressive Distributed Lag (ARDL) to determine both short-term and long-term effects. The results of the short-term analysis indicate that the variables of the number of tourist visits, hotel occupancy rates, and guest stay duration significantly affect PH as the dependent variable. However, for the dependent variable PR, the number of tourist visits and hotel occupancy rates are not significant, whereas guest stay duration is significant. In the long-term equation, none of the independent variables significantly influence the dependent variables PH or PR.